Vascular access and infection prevention and control: a national survey of routine practices in Irish haemodialysis units - Mc Cann, Margaret; Mellotte, George (My University, 2013)
Background National and international guidelines recommend the use of effective vascular access (VA) and infection prevention and control practices within the haemodialysis environment. Establishing an arterio-venous fistula (AVF) and preventing central venous catheter (CVC)-related infections are ongoing challenges for all dialysis settings. We surveyed VA and routine infection prevention and control practices in dialysis units, to provide national data on these practices in Ireland. Methods A descriptive survey was emailed to nurse managers at all adult (n = 19) and children (n = 1) outpatient haemodialysis units in the Republic of Ireland. Data collected included AVF formation, CVC insertion and maintenance practices, VA use and surveillance of infection and screening protocols. Nineteen of the 20 units responded to the survey. Results The AVF prevalence was 49% for 1370 patients in 17 units who provided these data [mean prevalence per unit: 45.7% (SD 16.2)]; the CVC mean prevalence per unit was 52.5% (SD 16.0). Fourteen dialysis units experienced inadequate access to vascular surgical procedures either due to a lack of dedicated theatre time or hospital beds. Six units administered intravenous prophylactic antimicrobials prior to CVC insertion with only two units using a CVC insertion checklist at the time of catheter insertion. Conclusion In general, dialysis units in Ireland show a strong adherence to national guidelines. Compared with the 12 countries participating in the Dialysis Outcomes Practice Patterns Study (DOPPS 4), in 2010, AVF prevalence in Irish dialysis units is the second lowest. Recommendations include establishing an AVF national prevalence target rate, discontinuing the administration of intravenous prophylactic antimicrobials prior to CVC insertion and promoting the use of CVC insertion checklists.
PUBLISHED
Keywords: infection prevention and control; haemodialysis; practice guidelines; survey; vascular access